Religious terminology in Romanian and confessional divisions - Klimkowski, Tomasz (Balcanica Posnaniensia. Acta et studia, 2020)
The article presents some terminological differences between various Christian denominations existing on Romanian territory, mainly between the Romanian Orthodox Church, prevalent in Romania, on the one hand and the Greek Catholic Church (the Uniats) and the Roman Catholic Church on the other. These differences are usually a result of a conscious linguistic policy of both Catholic rites and various Protestant and Neo-Protestant denominations. They are also reflected in the use of different forms of the name Jesus Christ, which exists in at least three versions. Even in the case of the same, common notions, the new denominations often introduce different terms, mainly Latin and Romance neologisms, in order to mark an external and formal difference from the Orthodox Church, whose terminology is of mostly Greek and Slavonic origin.